PENGALAMAN BERHARGA SELAMA MENJALANI PPL DI SMAN 16 MERANGIN - Hafzillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Field Experience Program (PPL) is a mandatory activity for education students to apply theoretical knowledge into real teaching practice at schools. The PPL program at SMAN 16 Merangin provided valuable experiences in understanding the educational environment, especially in teaching, school administration, and student interaction. During the implementation of the program, the student-teachers acted not only as classroom instructors but also participated in various school activities such as preparing lesson plans, extracurricular programs, and collaborating with supervising teachers and peers. This program offered opportunities to gain new insights into the responsibilities of an educator, improve pedagogical skills, and strengthen professional attitudes in teaching.